Pengaruh Tayangan Program Brownis TRANSTV terhadap Minat Menonton : Survei pada Ibu-ibu Warga RW 05 Pondok Pinang Centre Jakarta - Tengku Abdurrahman Rajak; Mulkan Habibi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
“Brownis” is a program that airs on TRANSTV. Brownis (Obrowlan Manis) is a talk show that airs on Trans TV since August 21, 2017 with the main hosts Ruben Onsu, Ayu Ting Ting and Wendi Cagur. This program discusses various coverage and styles. The purpose of this study is to measure the Influence of TRANSTV’s “Brownis” Program on Viewer Interest. The theories used in the Program are Format Power, Star Power, and Information Power. Including elements of Viewer Interest including Liking, Interest, Attention and Need. The approach in this study is quantitative, survey method. Data collection techniques are carried out by distributing questionnaires. Sampling uses the Probability Sampling technique. The collected data is then processed using SPSS version 23 to obtain accurate calculations. The conclusion is that TRANSTV’s “Brownis” Program has a significant influence on Viewer Interest with a t-count value (2.882) > t-table (1.992). With the percentage of the Event Program having an influence on Viewing Interest of 77.6% while the remaining 22.4% is influenced by other factors.